Germination and Growth Performance of Seedlings Of Ascorbic Acid, Silicon and Gibberellic Acid Treated Secondary Seed of Wheat Under Salt Stress (Bangladesh Agronomy Journal, 2022)
Considering the effect of salt stress on morph-physiological and biochemical changes of wheat (Triticum aestivum L. var. BARI Gom-26) as well as mitigation of the adverse effect through exogenous application of Ascorbic Acid (AsA), Silicon (Si) and Gibberellic Acid (GA3), the experiment was conducted at Department of Agronomy, Sher-e-Bangla Agricultural University, Dhaka, Bangladesh. In the field experiment, four levels of salt stress (0, 50, 80, 120 mM NaCl) were applied at 20 days after sowing and grown up to harvest. AsA (2 mM ascorbic acid), Si (200 μM SiO2), GA3 (100 μM gibberellic acid) were applied as foliar spraying at 20 days interval. Seeds were collected from the field experiment which used as secondary seeds as planting materials for second experiment to evaluate the influence of AsA, Si and GA3 on growth performance and physiological attributes of seedlings under salt stress. Experiment revealed that AsA, Si and GA3 enhanced the germination and growth performance of seedling under salinity stress. Overall, GA3 significantly increased the seed germination (%) and seedling growth parameters, while silicon mostly improved the fresh weight and chlorophyll (a, b and a+b) and AsA showed better relative water contents with other parameters. Considering the results of experiments, GA3 performed better than the AsA and Si in mitigating salt stress.Bangladesh Agron. J. 2022, 25(1): 115-128